Cricoteka – Theatrical Dimension of Architecture - Romaniak, Ewa Maria (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
The paper concerns the analysis of the building of Cricoteka in terms of theatricality, which is the role of architecture in the performance of city life. It discusses such aspects as the transfer of the idea of theatre onto architectural form, the dialogue with the viewer, the place of the building in the city and the influence of the object on the environment by generating tension between individual elements of composition solids. Theatrical dimension of architecture might be understood as a spectacle, invented and robust physiognomy, but also intriguing visual appeal. Through the versatile architectural costumes the architecture puts on, especially contemporary architecture, which stands out from the other buildings, tends to be incomprehensible to its recipients. Aiding the comprehension of the message, as well as its conscious shaping by the authors, is key to mutual understanding and establishing the dialogue. The detailed analysis of the building’s interior, which is the key aim of a project of Cricoteka, remains out of scope of this work.